Maximum power point estimation of MSX-60 poly-crystalline standalone solar PV system. (2023) - Singh, Bhuwan Pratap; Goyal, Sunil Kumar; Siddiqui, Shahbaz Ahmed
Abstract: In the recent decades, solar photovoltaic (PV) systems are one of the attractive renewable energy sources among the researchers. The maximum power generated by PV arrays varies with the variation in climatic conditions and exhibits non-linear P–V & I–V characteristics. Solar PV systems require external control to extract maximum power as their conversion efficiency is generally very low. The Maximum Power Point Techniques (MPPT) plays an important role to extract maximum power at every instant of time through an algorithm based automatic control. It automatically adjusts the power interface and extracts maximum possible power from PV array under variable irradiance, shading, and under variable temperature. The evaluation of performance of solar PV systems and MPPT techniques is become essential now days to enhance their performance under real–life variable atmospheric conditions. In additions to this, the performance of Perturb & Observe (P&O), one of the mostly used and robust MPPT techniques is analyzed in this work under continuously variable solar irradiance and temperature. Different patterns of variable solar irradiance are considered along with the real–life variable temperature throughout the day. The simulation has been carried out in MATLAB/Simulink 2020a to analyze the performance of P&O MPPT technique. Various performance parameters viz. Pout_max, Pout_avg, Ppv_max, Ppv_avg, Vout_max, Vout_avg, Vpv_max, Vpv_avg and conversion efficiency η are considered to analyze the performance of MPPT technique.